Effect of ethanolic extract of Euglena viridis on enzymatic profiles of Labeo rohita (Ham.) and protection against Aeromonas hydrophila infection - Pradhan, Jyotirmayee; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2022)
Effect of administration of ethanolic extract of Euglena viridis on liver enzyme profiles of Labeo rohita was investigated. Fish fingerlings were injected with the fractions of ethanolic extracts, viz., Ef1, Ef2 (5% ethylacetate/hexane), Ef3 (10% ethylacetate/hexane) and Ef4, Ef5 (30% ethylacetate/hexane) of Euglena viridis. The treated fish were challenged with Aeromonas hydrophila to assess the survival rate and enzyme profile. The serum samples were assayed for activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and acid phosphatase (ACP) enzymes. Results showed no significant difference in ACP activity between the pre-challenged 5% ethylacetate/hexane and 10% ethylacetate/hexane injected group and control. Similar insignificant variation in ALT activity was observed in all the exposure periods before the challenge. Significantly (pâ‰¤0.05) different AST activity was observed in all the injected groups on the 10th day post-challenge in comparison to the control. On 10 days of post- challenge, survival of fish that received the fractions of ethanolic extracts of E. viridis with 5% ethylacetate/ hexane and 30% ethylacetate/hexane was significantly higher than the control fish. The results suggest that Euglena extract enhances the resistance of L. rohita against A. hydrophila and has the potential for use in health management in fish.Key words Aeromonas hydrophila; Alkaline phosphatase; Euglena viridis; Immunostimulation